Pengembangan Potensi Daerah dengan Loka Karya dan Penyuluhan Koperasi Unit Desa di Kecamatan Sekala Berak Kabupaten Lampung Barat - Erlina Rufaidah (Balitbangda Provinsi Lampung, 2015)
The general objective of this community service is to develop the potential of underutilized Batu Berak sub-district. While the specific objectives to be achieved is (1) increasing the role of the community in the village cooperative unit by holding workshops and counseling about cooperative economic models tha include : provision of venture capital and marketing of products. This community service using research and development model developed by Brog and Gall implemented within two years of activity. First year, is the model development stage, based on the data obtained in the initial counseling, designing the initial model, do a comparative study, observation, revision and generating method of region potention with village cooperative unit workshops and counseling. Second year, sosialize, test the method of region potention with village cooperative unit workshops and counseling. The expected outcome of this community service is formed of society mindset about utilization of cooperative as a foundation of the economy and improve people standards of living by working with village cooperative unit.